Audit Delay in the Perspective of Company Size, Profitability, and Solvency - Eka Andryani Sri Winarsih (Value Relevance: Jurnal Akuntansi, 2024)
An audit delay indicates the completion of the finance company's audit report. The condition company also follows the determined audit schedule because it relates to the condition finance company. This research analyzes the influence of company size, Profitability, and solvency on audit delay. The population of this research is in the manufacturing sector and food and beverage companies listed on the Indonesian Stock Exchange in 2019-2023, with 120 observations. This type of research data uses secondary data sourced from reports of annual companies. Method analysis uses analysis regression, which covers classical assumptions, regression models, test hypotheses, and determinant coefficients. Results show that Profitability and solvency are influential against audit delays, while the size of the company has no influence against audit delays. The contribution of research models explains audit delay of 63.11 %